A retrospective single centre audit on gastric gastrointestinal stromal tumours over a period of fifteen years - Kuhn, Suzanne (Division of General Surgery, 2023)
Introduction: Gastrointestinal stromal tumours (GIST) are the commonest tumour of mesenchymal origin; favour the stomach, and account for a very small percentage of gastrointestinal tract tumours. Methods: In this retrospective audit of GISTs presenting to the Groote Schuur Hospital surgical and oncological multidisciplinary team (MDT) between 2004 – 2019, gastric GISTs were evaluated as regards presentation, gastric anatomical position, histological subtype with risk stratification, management and outcomes. Results: Of 126 GIST tumours presenting to this MDT, 82 originated in the stomach. Complete histopathological records could be obtained for 64. With an average of 59 years (50 male: 32 female), 18 (28%) presented with a herald bleed. Other common presentations included anaemia, epigastric mass and pain. The tumours were predominantly found in the body and fundus (64%), with a spindle cell subtype predominance (41%). The association between cancer cell subtype and gastric position was not significantly different (p=0.728). Cystic degeneration was found on 11 (17%) analyzed and cell necrosis on 12 (18%). These findings were not related to larger tumor size or prognosis. Five required downstaging with Imatinib prior to surgery. Thirty-seven patients underwent a surgical procedure: 24 wedge resections and 12 anatomical resections. Risk stratification was performed with the modified National Institutes of Health (NIH/Fletcher) score. Twenty-eight cases had inaccurate mitotic counts and couldn't be scored, 17 scored high risk, 9 intermediate risk, 9 low risk and 1 very low risk. Ten patients died of metastatic disease, 34 were discharged with no disease progression after 3 years, 1 patient with disease progression currently remains on Imatinib, and 19 were lost to follow up. Conclusion: Gastric GISTs appear to have a predilection for the proximal stomach; it is unsure whether this is purely due the greater surface area. The spindle cell subtype dominated in the proximal gastric GISTs. Cystic degeneration and cell necrosis did not seem to be related to larger tumours or outcomes.